Introduire le lexique spécialisé dès l’initiation en français scientifique - Olmo Cazevieille, Françoise (Didáctica. Lengua y Literatura, 2007)
The idea of exposing students to specialized lexical elements at beginners’ level stems from an analysis of the needs of the institution and society, but above all, from the students’ needs. They, as a specialized audience, should certainly be able to use French for professional purposes. How could an engineer or researcher be considered an expert if s/he cannot use the language like experts do? In this article we put forward a reflective methodology as well as a pedagogical proposal for students at beginner’s level, after the introduction of several theoretical observations. Our proposal comes in four parts. We will start with an introduction and presentation of the lexical units that make up for the basic lexical elements required for students to achieve an understanding of specialized texts, to later end up working with authentic texts for French engineers in both a written or electronic format. La idea de introducir el léxico especializado ya en el nivel de iniciación, surge del análisis de necesidades de la institución y de la sociedad, pero sobretodo, de los aprendices. Este público de perfil científico deberá ciertamente utilizar el idioma extranjero para fines profesionales. Y, ¿cómo puede ser considerado especialista un ingeniero o un investigador que no sepa expresarse como un verdadero especialista? Lo que proponemos en este artículo consiste, tras exponer algunas observaciones teóricas, en presentar nuestra reflexión metodológica así como una propuesta pedagógica para los niveles de principiantes. Esta propuesta consta de cuatro etapas o partes. Empieza con la introducción y explicitación del léxico de baja especialización, imprescindible para entender los textos de especialidad y, acaba con la explotación de textos auténticos escritos para ingenieros francófonos en soporte papel o en formato electrónico.